Predictors for poor daily weight gain in preterm neonates exposed to different dose regimens of caffeine in ICU- a retrospective cohort study - Saeed Ahmed; Ayaz ur Rehman; Zainab Bibi; Sundus Iftikhar; Maleeha Raza; Hafiz Mohammad Amir Yousuf; Fizzah Naz; Syed Adil Mir Shah; Syeda Lamiya Mir; Ayesha Bibi; Wasif Ahmed Khan; Muhammad Sohail Salat; et al. (BMC, 2024)
Abstract Background With a wide therapeutic index, efficacy, ease of use, and other neuroprotective and respiratory benefits, caffeine citrate(CC) is currently the drug of choice for preterm neonates (PTNs). Caffeine-induced excessive energy expenditure, diuresis, natriuresis, and other CC-associated potential side-effects (CC-APSEs) result in lower daily-weight gain (WG) in premature neonates. This study aimed to evaluate the risk factors for daily-WG in neonates exposed to different dose regimens of caffeine in ICU. Method This retrospective cohort study included neonates of ≤ 36weeks gestational age (GA) and received CC-therapy. The same participants were followed for data analysis in two postnatal phases: 15-28 and 29-42 days of life (DOL). Based on daily CC-dose, formed group-I (received; standard-doses = 5 mg/kg/day), group-II (received;>5-7 mg/kg/day), and group-III (received;>7 mg/kg/day). Prenatal and postnatal clinical characteristics, CC-regimen, daily-WG, CC-APSEs, and concomitant risk-factors, including daily-caloric intake, Parenteral-Nutrition duration, steroids, diuretics, and ibuprofen exposure, were analyzed separately for group-II and group-III using group-I as standard. Regression analysis was performed to evaluate the risk factors for daily-WG. Results Included 314 PTNs. During 15-28 DOL, the mean-daily-WG(MD-WG) was significantly higher in group-I than group-II [19.9 ± 0.70 g/kg/d vs. 17.7 ± 0.52 p = 0.036] and group-III [19.9 ± 0.70 g/kg/d vs. 16.8 ± 0.73 p < 0.001]. During 29-42 DOL the MD-WG of group-I was only significantly higher than group-III [21.7 ± 0.44 g/kg/d vs. 18.3 ± 0.41 g/kg/d p = 0.003] and comparable with group-II. During 15-28 DOL, observed CC-APSEs was significantly higher in group-II and III but during 29-42 DOL it was only significant in group-III. In the adjusted regression analysis for daily-WG during 15-28DOL, with respect to standard-dose, 5-7 mg/kg/day (β=-1.04; 95%CI:-1.62,-0.93) and > 7-10 mg/kg/day (β=-1.36; 95%CI:-1.56,-1.02) were associated with a lower daily-WG. However, during 29-42DOL, this association was present only for > 7-10 mg/kg/day (β=-1.54; 95%CI:-1.66,-1.42). The GA ≤ 27weeks (β=-1.03 95%CI:-1.24, -0.88) was associated with lower daily-WG only during 15-28DOL. During both periods of therapy, higher cumulative-caffeine dose and presence of culture proven sepsis, tachypnea, hyponatremia, and feeding intolerance were significantly associated with lower daily-WG. Conversely, daily kcal intake was found to be linked with an increase in daily-WG in both periods. Conclusion In this study cohort exposure to higher caffeine daily and cumulative doses is associated with lower postnatal daily-WG in PTNs than standard-daily doses, which may be due to its catabolic effects and CC-APSEs.